A Systematic Review of Intercultural Communication Competence Development in CEFR- Aligned English Proficiency Textbooks - Sahar, Rafidah (Kulliyyah of Languages and Management Press, 2023)
The Common European Framework of Reference for Languages (CEFR) is a well-established outline that describes language learners’ abilities to use language and categorises what a learner can do using a six-point scale from basic users (A1) to proficient users (C2). CEFR offers a structure for developing language curriculum and syllabus, textbook, testing, and measuring and evaluating learning outcomes from kindergarten to tertiary levels (Little, 2016). As CEFR gains prominence within the curriculum and the global landscape becomes increasingly diverse, the question arises as to whether the learning resources in CEFR-aligned English textbooks adequately address ICC’s objectives and provide a comprehensive representation of cultural knowledge. Hence, the primary objective of this systematic review is to analyse current studies that investigate the incorporation of cultural material within English textbooks aligned with the CEFR framework, explicitly focusing on university-level students. The anticipated outcomes of this review are poised to provide a more lucid understanding of the prevailing theoretical and pedagogical challenges concerning integrating cultural elements into CEFR-aligned textbooks and ultimately seek to augment the level of ICC of university students.